SARS‐COV‐2 genomic monitoring in the state of São Paulo unveils two emerging AY.43 sublineages. Issue 7 (12th March 2022) - Lima, Alex Ranieri Jerônimo; Ribeiro, Gabriela; Viala, Vincent Louis; de Lima, Loyze Paola Oliveira; Martins, Antonio Jorge; Barros, Claudia Renata dos Santos; Marqueze, Elaine Cristina; Bernardino, Jardelina de Souza Todao; Moretti, Debora Botequio; Rodrigues, Evandra Strazza; Santos, Elaine Vieira; Brassaloti, Ricardo Augusto; et al.
Abstract: Delta VOC is highly diverse with more than 120 sublineages already described as of November 30, 2021. In this study, through active monitoring of circulating severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) variants in the state of São Paulo, southeast Brazil, we identified two emerging sublineages from the ancestral AY.43 strain which were classified as AY.43.1 and AY.43.2. These sublineages were defined by the following characteristic nonsynonymous mutations ORF1ab:A4133V and ORF3a:T14I for the AY.43.1 and ORF1ab:G1155C for the AY.43.2 and our analysis reveals that they might have a likely‐Brazilian origin. Much is still unknown regarding their dissemination in the state of São Paulo and Brazil as well as their potential impact on the ongoing vaccination process. However, the results obtained in this study reinforce the importance of genomic surveillance activity for timely identification of emerging SARS‐CoV‐2 variants which can impact the ongoing SARS‐CoV‐2 vaccination and public health policies.